2019
DOI: 10.1111/jog.14145
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and symptomatic relief following ultrasound‐guided transvaginal radiofrequency ablation in patients with adenomyosis

Abstract: Aim To report the reproductive results and symptomatic relief of patients with adenomyosis who attempted to conceive after ultrasound‐guided radiofrequency ablation (RFA). Methods Of 182 consecutive patients with adenomyosis who had undergone RFA, only 81 patients were eligible for this study. Pregnancy outcomes, postoperative complications, preoperative and postoperative pictorial blood loss assessment chart scores, and pain scores were evaluated. Results Of these 81 patients, 74 were infertile and seven were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
(40 reference statements)
0
22
1
Order By: Relevance
“…Both the VAS and SSS scores significantly decreased after the combined treatment and were maintained at a very low level during the 3-year follow-up. It is difficult to compare the present results with the previous studies in which RFA was solely applied because the severity of the adenomyosis and follow-up period are different [4][5][6]. The results in our study also showed that the mean uterine volume significantly decreased by 57% at 1 year after procedure.In the previous studies, the 1-year uterine volume reduction rate of single RFA was 41 À 47% [4][5].…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Both the VAS and SSS scores significantly decreased after the combined treatment and were maintained at a very low level during the 3-year follow-up. It is difficult to compare the present results with the previous studies in which RFA was solely applied because the severity of the adenomyosis and follow-up period are different [4][5][6]. The results in our study also showed that the mean uterine volume significantly decreased by 57% at 1 year after procedure.In the previous studies, the 1-year uterine volume reduction rate of single RFA was 41 À 47% [4][5].…”
Section: Discussioncontrasting
confidence: 73%
“…Image-guided tumor ablation techniques (radiofrequency, microwave and high-intensity focused ultrasound) have been introduced for the treatment of adenomyosis in the recent years. The safety and effectiveness of this relatively new strategy for adenomyosis is under evaluation [4][5][6][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 38 articles , met all inclusion criteria and were included in this meta-analysis. The types of ablation were HIFU in 28 studies , PMWA in five studies [46][47][48][49][50] and RFA in four studies [51][52][53][54]. Besides, one study [45] compared PMWA with RFA in the management of AD.…”
Section: Literature Searchmentioning
confidence: 99%